Tigecycline: Alone or in combination?. Issue 7 (2nd July 2016) - Cai, Yun; Bai, Nan; Liu, Xu; Liang, Beibei; Wang, Jin; Wang, Rui
Abstract: Background The broad spectrum antibiotic tigecyline has promising efficacy against many multidrug-resistant (MDR) pathogens. However, when used clinically, many reports about treatment failures of tigecycline monotherapy indicate that it might not be sufficient to control severe infections. Combination therapy has become an option to treat infection with MDR bacteria because of the distinct advantage in terms of broad coverage, synergistic effect and prevention of drug resistance development. Methods Search terms 'tigecycline', 'GAR-936' and 'glycylcycline' combined with the term 'combination' were applied to retrieve the available in vitro and in vivo studies on tigecycline combination therapy from PubMed database (January 1993–August 2015). Results Colistin-tigecycline was the most studied combination and showed promising efficacy. Other combination regimens, such as tigecycline plus sulbactam, carbapenem or rifampicin, also showed synergistic effects against different bacteria. However, most of the data was from in vitro and animal studies. Only some case reports indicated that tigecycline containing combination therapy had favourable outcomes. Conclusions Although this study could not conclude that combination therapy with tigecycline was superior to monotherapy, when severe infection leaves no other choice, selection of combination drugs according to infection status and in vitro susceptibility testing is recommended. There is a great need for well-designed studies to evaluate the effectiveness and safety of combination therapy compared to tigecyline monotherapy.